The Effect of Game-Based Learning Model Supported by ROMERE Teaching Aids on Elementary School Students' Learning Activity - Jannah, Miftahul; Malihatul Hawa, Anni (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
This study aims to determine the effect of the Game-based Learning model supported by ROMERE teaching aids on student learning activity. This study used a quantitative approach with an experimental method type, namely Quasi-Experimental Design with a Non-equivalent Control Group design form. The research population involved all students at SDN Langensari 02 Ungaran Barat, consisting of class III A students (as a control class) and class III B students (as an experimental class). The data collection technique used was non-test, in the form of questionnaire sheets, observation sheets, unstructured interview sheets, and documentation (photos/pictures). The data analysis techniques used were the Independent Sample T-Test and the Simple Linear Regression Test. The research results revealed an effect of using the Game-Based Learning model supported by the ROMERE teaching aids on student learning activity. This can be proven from the Simple Linear Regression Test with a sig value of less than 0.05, namely 0.001 <0.05. Therefore, it can be concluded that applying the Game-Based Learning model supported by ROMERE teaching aids influences student learning activity. Furthermore, the simple linear regression test revealed an R square R² = 0.401, or 40.1%, indicating that the variable of the Game-Based Learning model supported by ROMERE teaching aids accounts for 40.1% of the variation in learning activity, with the remainder influenced by other variables.